Inhalant Mammal-Derived Lipocalin Allergens and the Innate Immunity - Virtanen, Tuomas (Frontiers in Allergy, 2022)
A major part of important mammalian respiratory allergens belongs to the lipocalin family of proteins. By this time, 19 respiratory mammalian lipocalin allergens have been registered in the WHO/IUIS Allergen Nomenclature Database. Originally, lipocalins, small extracellular proteins (molecular mass ca. 20 kDa), were characterized as transport proteins but they are currently known to exert a variety of biological functions. The three-dimensional structure of lipocalins is well preserved, and lipocalin allergens can exhibit high amino acid identities, in several cases more than 50%. Lipocalins contain an internal ligand-binding site where they can harbor small principally hydrophobic molecules. Another characteristic feature is their capacity to bind to specific cell-surface receptors. In all, the physicochemical properties of lipocalin allergens do not offer any straightforward explanations for their allergenicity. Allergic sensitization begins at epithelial barriers where diverse insults through pattern recognition receptors awaken innate immunity. This front-line response is manifested by epithelial barrier-associated cytokines which together with other components of immunity can initiate the sensitization process. In the following, the crucial factor in allergic sensitization is interleukin (IL)-4 which is needed for stabilizing and promoting the type 2 immune response. The source for IL-4 has been searched widely. Candidates for it may be nonprofessional antigen-presenting cells, such as basophils or mast cells, as well as CD4+ T cells. The synthesis of IL-4 by CD4+ T cells requires T cell receptor engagement, i.e., the recognition of allergen peptides, which also provides the specificity for sensitization. Lipocalin and innate immunity-associated cell-surface receptors are implicated in facilitating the access of lipocalin allergens into the immune system. However, the significance of this for allergic sensitization is unclear, as the recognition by these receptors has been found to produce conflicting results. As to potential adjuvants associated with mammalian lipocalin allergens, the hydrophobic ligands transported by lipocalins do not appear to be mandatory while it is justified to suppose that lipopolysaccharide plays a role in the sensitization. Taken together, type 2 immunity to lipocalin allergens appears to be an aberrant immune response resulting from a combination of signals involving both the innate and adaptive immunities.